การศึกษาการรับรู้เรื่องทักษะชีวิตและสภาพการจัดการเรียนรู้เกี่ยวกับทักษะชีวิตของครู - โกศลเวช นรัญจ์; แกมเกตุ รศ.ดร.วรรณี (An Online Journal of Education, 2015)
การวิจัยครั้งนี้ใช้วิธีการวิจัยเชิงคุณภาพ (qualitative research) มีวัตถุประสงค์เพื่อศึกษาการรับรู้เรื่องทักษะชีวิตและสภาพการจัดการเรียนรู้เกี่ยวกับทักษะชีวิตของครู ตัวอย่างวิจัยเป็นครูโรงเรียนที่เป็นกรณีศึกษา จำนวน 3 โรงเรียน และผู้ให้ข้อมูลที่มีการจัดการเรียนการสอนแบบบูรณาการร่วมกับความรู้ด้านทักษะชีวิตที่ดีตามเกณฑ์ ซึ่งเป็น ในโรงเรียนสังกัดกองบัญชาการตำรวจตระเวนชายแดน สังกัดสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน และสังกัดกรุงเทพมหานคร จำนวน 16 คน เครื่องมือวิจัย คือ แบบสัมภาษณ์การรับรู้ด้านทักษะชีวิต ผลการวิจัยพบว่า 1) นิยามทักษะชีวิตตามการรับรู้ หมายถึง (1) ความสามารถหรือทักษะที่นำไปใช้ในการดำรงชีวิตประจำวัน (2) ความสามารถในการดำเนินชีวิตได้อย่างมีความสุข บรรลุเป้าหมาย ประสบผลสำเร็จและมีคุณภาพชีวิต และ (3) ความสามารถที่ใช้ในการทำงานและประกอบอาชีพ 2) ทักษะชีวิตที่เหมาะสมกับนักเรียนตามการรับรู้ ประกอบด้วย (1) ความรู้เรื่องการส่งเสริมสุขภาพ (2) ความรู้เรื่องอาหารและโภชนาการ และ (3) ทักษะพื้นฐานการทำงาน 3) สภาพการจัดการเรียนรู้เกี่ยวกับทักษะชีวิตของครู ประกอบด้วย (1) การสร้างและพัฒนาโดยกระบวนการเรียนการสอน และ (2) การสร้างและพัฒนาผ่านการฝึกปฏิบัติและประสบการณ์ This research with qualitative research methodology. The objectives of this study were a study on perceptions of life skills and learning management circumstances about life skills of teachers that example case study research were school teachers of 3 schools. And Informants delivered data of Integrated Management Education corporate with good life skills on main principle. Which were Border Patrol Police School, School under the Office of Basic Education Commission and School under the Bangkok Metropolitan Administration 16 people. The research instrument was questionnaires on perception of life skills. The finding in this study revealed the followings : 1) definition of life skills on perception meaning (1) competency or skill to apply in daily life (2) competency to happiness live , achieve and quality of life and (3) competency to apply working and earn a living 2) life skills be proper with student according to perception consist (1) knowledge base of permit health (2) understanding of food and nutrition and (3) knowledge and base skills of working 3) learning management circumstances about life skills of teachers that consist (1) create and develop with process of study and (2) create and develop carry on practice and experience.